The Effectiveness of Mufradat Cards in Arabic Learning Outcomes in Thematic Learning in Madrasah Ibtidaiyah - Suwardi Suwardi; M. Farid Abdullah; Syaefudin Achmad (LISANIA: Journal of Arabic Education and Literature, 2023)
Arabic learning outcomes in Madarasah Ibtidayah (MI) are still relatively low. This study aims to improve Arabic learning outcomes in MI by using mufradat (Arabic Vocabulary) cards in thematic learning. This research used experimental research with true experimental design. The respondents of this study included five teachers and 107 first grade students of private MIs in Salatiga City. Data collection methods included interviews with an interview guideline instrument and tests with a test instrument that has been declared valid and reliable. Qualitative data were analyzed by reviewing, reducing, categorizing, interpreting  the data, and drawing conclusions. While quantitative data were analyzed with SPSS using the Cronbach's Alpha formula, Test of Homogeneity of Variances, ANOVA, t-test, and omega squared two independent samples. The theoretical contribution of this research is the specification of mufradat cards used for Arabic learning in thematic learning of grade I MI which includes specifications of card components and specifications of mufradat components. This study concluded that the use of mufradat cards has been proven effective to improve Arabic learning outcomes in thematic learning of grade I MI with an effectiveness value of 54.43%. This study recommends that to improve Arabic learning outcomes in MI, mufradat cards should be included in thematic learning.